The sounds of early eighteenth-century pastoral: Handel, Pope, Gay, and Hughes - Jeffrey HOPES (E-REA)
In the early eighteenth century the composer George Frideric Handel and the poets Alexander Pope, John Gay and John Hughes all engaged with the language and aesthetics of pastoral. Alexander Pope published his Pastorals in 1709, John Gay his Shepherd’s Week in 1714 and John Hughes the texts for six English Cantatas which were published after his death in 1735. The poetry of Pope presents a sophisticated Virgilian pastoral soundscape whereas that of John Gay portrays the more rustic sounds of mock pastoral in imitation of Spenser. Handel composed two works on the myth of Acis, Galatea and Polyphemus, the first (Aci, Galatea et Polifemo) before he left Italy, in 1708, the second (Acis and Galatea) when he was in residence at Cannons, the London house of James Brydges, Earl of Carnarvon, in 1718. Between them his pastoral opera Il pastor fido was performed in 1712. Handel’s music builds a pastoral language that draws on the conventions of the genre but which constantly subverts and manipulates them for dramatic and psychological effect. In Acis and Galatea, Gay, Hughes and possibly Pope, who collaborated on the libretto, joined Handel in creating a new and consciously English pastoral language.